EVALUATION OF GENETIC VARIABILITY HERITABILITY AND GENETIC ADVANCES IN GLADIOLUS (GLADIOLUS GRANDIFLORUS L.) GENOTYPES - G. B. BHUJBAL; N. G. CHAVAN; S. S. MEHETRE (The Bioscan, 2013)
Assessment of variability, heritability and genetic advances of 31 gladiolus genotypes were evaluated. The presence of high amount of variability for all characters except sprout per corm and number of side spikes in the 31 gladiolus genotypes was recorded. The heritability of different field characters was categorized as very high which ranged between 23.40% (sprouts per corm) to 96.10% (florets per spike). Very high heritability coupled with high genetic advance for spike length, days to 50 per cent flowering, plant height advocated high genetic progress for them. It was concluded that highly significant varietal differences indicated the presence of high amount of variability.